Features of disease course of some forms of herpesvirus infection - Sorokina, O G; Popov, M M; Liadova, T I; Malanchuk, S H; Dorosh, D M; Sorokina, A V (Annals of Mechnikov's Institute, 2020)
Among the many factors that directly affect the immune system, infections caused by the herpes virus deserve special attention. In recent years, there has been an increase in the number of patients suffering from chronic recurrent herpesvirus infections, which in many cases are accompanied by severe general malaise and a number of therapeutic complaints. Today about 80-95% of the population is infected with Epstein-Barr virus EBV. Primary infection of EBV leads to lifelong persistence of the pathogen with possible periodic reactivation under the action of various immunosuppressive factors, which leads to chronic forms of the disease. EBV can cause chronic manifest and erased forms of the disease, running on the type of chronic mononucleosis. Thus, the study of the nature of clinical and laboratory changes in patients with chronic EBV infection and the peculiarities of the disease is an urgent problem of our time. The aim of this work was to study the features of the course of chronic EBV infection. We performed a comprehensive clinical and laboratory examination of 128 patients with chronic EBV infection (reactivation period). The diagnosis of chronic EBV infection was established on the basis of medical history, complaints, the presence of specific antibodies to EBV antigens and the detection of virus DNA in the blood. Studies of clinical blood tests of patients with chronic EBV infection and the control group showed differences. Thus, in patients with chronic EBV infection, a significantly elevated ESR level was found - 12.6 ± 1.8 versus 4.5 ± 1.1 inthe control group (p <0.05). The levels of erythrocytes, hemoglobin and platelets did not differ significantly from the control group. In patients with chronic EBV infection, there was a decrease in the level of leukocytes (5.13 ± 0.22) x 109/ l against (6.20 ± 1.8) x 109/l in the control group (p> 0.05), but these changes did not go beyond the norms established for healthy people. Analysis of the leukocyte formula revealed the presence of patients with chronic WEB infection with a significant increase in the relative content of lymphocytes - 42.50 ± 2.0% against 33.70 ± 2.68% (p <0.05) and monocytes - 11.15 ± 0.9% vs. 3.0 ± 0.6% (p <0.05), which was the basis for confirming the presence of a chronic infectious process. In general, 94.8% of patients with chronic EBV infection had lymphocytosis and 82.5% had monocytosis. The relative number of neutrophils in patients with chronic WEB infection averaged 45.35 ± 4.1% against 61.7 ± 3.8% in the control group (p <0.05); the relative number of eosinophils and basophils was within normal limits. When studying the absolute number of lymphocytes and monocytes in patients with chronic EBV infection, there was a tendency to increase them and their level was on average (2.13 ± 0.7) x 109/ l and (0.51 ± 0.08) x 109/ l against (2.39 ± 0.7) x 109/ l and (0.47 ± 0.08) x 109/ l in the control group (p> 0.05). The absolute number of neutrophils in patients with chronic WEB infection was significantly lower than in the control group and was 2.70 x 109/ l versus 4.21 x 109/ l (p <0.05). The study of the absolute number of eosinophils and basophils in patients with chronic EBV infection did not reveal statistically significant differences compared with the control group. Thus, according to the results of our study, we found that patients with chronic EBV infection among the clinical manifestations were most often chronic tonsillitis, chronic fatigue syndrome and peripheral lymphadenopathy. Analysis of the results of laboratory studies revealed a significant increase in ESR, relative lymphocytes and monocytes, as well as a decrease in absolute and relative neutrophils, compared with the control group of patients, indicating a shift in white blood cell count, characteristic of the viral etiology of the disease what associated with the EBV. DOI: 10.5281/zenodo.4038961